Preparation method of coal gangue autoclaved aerated concrete and application of modifier of coal gangue autoclaved aerated concrete

By using regulators such as silica fume and silica sol in the autoclaved aerated concrete of coal gangue, the activity and hydration reaction activity of coal gangue are improved, and the problems of low compressive strength and environmental pollution in the preparation of coal gangue are solved, and the problem of low compressive strength and environmental pollution is achieved. Efficient and environmentally friendly autoclaved aerated concrete preparation.

CN119161119AActive Publication Date: 2024-12-20PENGYANG COUNTY XINZHUO ENERGY TECH DEV CO +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311786429.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2024-12-20
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

In the prior art, coal gangue has low compressive strength when preparing autoclaved aerated concrete, which has failed to effectively solve the environmental pollution caused by spontaneous combustion of coal gangue, and is difficult to be used stably in industrialization.

Method used

The regulators of coal gangue autoclaved aerated concrete are used, including silica fume, silica sol, sodium tripolyphosphate, glass fiber powder, hydroxypropyl methyl cellulose and lignin sulfonate, and are treated and regulated by decarbonization. The combination of the coal gangue improves the activity and hydration reaction activity of coal gangue, and enhances the compressive strength and durability of the products.

Benefits of technology

It significantly improves the compressive strength of coal gangue autoclaved aerated concrete, complies with national quality standards, reduces preparation costs, solves environmental pollution problems, and extends the service life of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161119A_ABST
    Figure CN119161119A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of coal gangue autoclaved aerated concrete and application of a modifier of the coal gangue autoclaved aerated concrete. The modifier comprises one or a combination of more of silica fume, silica sol, sodium tripolyphosphate and the like. The invention relates to coal gangue autoclaved aerated concrete. The coal gangue autoclaved aerated concrete is prepared from the following raw materials: coal gangue accounting for more than 50% of the total mass of the raw materials of the coal gangue autoclaved aerated concrete. The invention relates to a method for preparing autoclaved aerated concrete from coal gangue, which comprises the following steps: step 1, carrying out decarburization treatment on the coal gangue, the decarburization treatment comprising photoelectric separation and / or washing flotation; after decarburization treatment, the carbon content of the gangue is below 7%; and step 2, mixing and stirring the raw materials of the coal gangue autoclaved aerated concrete, and then carrying out pouring and standing, cutting and demolding, pre-curing in front of a kettle and autoclaved curing to obtain the autoclaved aerated concrete. According to the method disclosed by the invention, through multi-stage decarburization and single-doping and multi-doping composite doping regulator, the influence of low carbon content and coal gangue activity can be greatly shielded or reduced, and the compressive strength of the product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a technology for preparing autoclaved aerated concrete, in particular to a technology for preparing autoclaved aerated concrete using coal gangue. Background Art

[0002] With the rapid development of industry and infrastructure projects, a large amount of solid waste is also generated. Coal gangue is a kind of solid waste separated in the process of coal mining. It is a black-gray rock associated with coal in the process of coal formation. The main mineral components of coal gangue are clay minerals (kaolinite, montmorillonite, illite, etc.), quartz, dolomite, pyrite and other minerals. The harm caused by the accumulation of a large amount of coal gangue to the environment is obvious, such as land occupation, surface subsidence, soil erosion, geological desertification and ecological damage. The accumulation and long-term exposure of coal gangue can also easily cause it to spontaneously combust, thereby generating dust and harmful gas emissions (CO, CO2, SO2, H2S) and other serious environmental problems.

[0003] At present, my country's coal gangue is mainly used in road construction, power generation, and building materials, accounting for 56%, 32%, and 12% of the total utilization rate of coal gangue respectively. Therefore, improving the application of coal gangue in building materials is an important way to utilize coal gangue resources, comprehensively manage the environment, promote social development, and improve the economy.

[0004] The unit volume weight of autoclaved aerated concrete blocks is one-third of that of clay bricks, the thermal insulation performance is 3-4 times that of clay bricks, the sound insulation performance is 2 times that of clay bricks, the anti-seepage performance is more than 1 times that of clay bricks, and the fire resistance performance is 6-8 times that of reinforced concrete. The masonry strength of the blocks is about 80% of the strength of the blocks themselves (30% for red bricks). It is particularly suitable for internal and external filling walls of high-rise buildings and internal filling walls below the ground (except for walls with special requirements), and the construction characteristics are also very good.

[0005] Autoclaved aerated concrete is a porous silicate product made of siliceous and calcareous materials as the main raw materials, mixed with gas-generating agents, through processes such as raw material preparation, batching and pouring, gas generation and quiescence, cutting and forming, autoclaving and curing, sorting and packaging. Its typical feature is that the pores in the product are formed by chemical reactions.

[0006] The raw materials used to produce autoclaved aerated concrete are divided into four categories: basic materials, gas-generating materials, regulating materials and structural materials. The basic materials are the main materials that form autoclaved aerated concrete, accounting for more than 95% of the total weight of the product, including siliceous materials (the main component is SiO2) and calcareous materials (the main component is CaO). The source of siliceous raw materials is quartz sand, accounting for 55% to 65% of the product weight. The source of calcareous raw materials is mainly cement and lime, accounting for more than 30% of the product weight.

[0007] Since sand is a non-renewable mineral resource, the development of coal gangue to replace siliceous materials has not only found an effective way to save energy, save soil, utilize waste, and protect the environment, but also found a sustainable development path for autoclaved aerated concrete production enterprises to reduce costs and improve efficiency. The volcanic ash activity of the original coal gangue is very low, which hinders the application of coal gangue in the preparation of autoclaved aerated concrete. After spontaneous combustion, the problem of high carbon content of coal gangue can be basically solved, and the activation problem of raw materials can be improved to a certain extent. However, the carbon dioxide, sulfur dioxide, nitrogen oxides and smoke emitted during the combustion process will seriously pollute the atmospheric environment. At the same time, the spontaneous combustion of coal gangue has greater regionality, specificity and incompleteness. Therefore, the spontaneous combustion or combustion method cannot solve the problem of industrial application of coal gangue in the preparation of autoclaved aerated concrete. At the same time, in the relevant technology, the use of coal gangue to prepare autoclaved aerated concrete often has low compressive strength and does not meet the relevant national standards. Therefore, there is an urgent need to study a technology for preparing autoclaved aerated concrete by adding coal gangue in a large amount to the raw materials for preparing autoclaved aerated concrete. This technology can be stably applied in industrialization, and the obtained products have high compressive strength and meet national quality standards. Summary of the invention

[0008] The present invention aims to solve the problems existing in the related art of preparing autoclaved aerated concrete using coal gangue, and provides a technology for preparing autoclaved aerated concrete using coal gangue in a larger dosage, and the obtained product has high compressive strength and meets national quality standards.

[0009] In view of the above-mentioned limitations, the present invention proposes a regulator for gangue autoclaved aerated concrete, gangue autoclaved aerated concrete and a preparation method thereof.

[0010] A regulator for gangue autoclaved aerated concrete, wherein the regulator is selected from:

[0011] Group 1: Silica Fume;

[0012] and / or, Group 2: silica sol;

[0013] The regulator accounts for 3.0% to 15.0% of the total mass of the raw materials of the gangue autoclaved aerated concrete.

[0014] Furthermore: if the regulators are a first group and a second group, the mass ratio of the first group to the second group is (2:3) to (5:2).

[0015] A regulator for gangue autoclaved aerated concrete, wherein the regulator is selected from:

[0016] Group 1: Silica Fume;

[0017] and / or, at least one of the second group, the third group, and the fourth group;

[0018] The second group is silica sol;

[0019] The third group is sodium tripolyphosphate;

[0020] The fourth group is at least one of glass fiber powder, hydroxypropyl methylcellulose, and lignin sulfonate;

[0021] The regulator accounts for 3.0% to 15.0% of the total mass of the raw materials of the gangue autoclaved aerated concrete.

[0022] Further: if the regulator includes the first group and the third group, the mass ratio of the first group to the third group is 5:2;

[0023] Furthermore: if the regulator includes a first group and a fourth group, the mass ratio of the first group to the fourth group is (5:1) to (5:4).

[0024] A kind of gangue autoclaved aerated concrete, the raw materials of the gangue autoclaved aerated concrete include:

[0025] Coal gangue, the mass of the coal gangue accounts for more than 50% of the total mass of raw materials of the coal gangue autoclaved aerated concrete; the carbon content of the coal gangue is less than or equal to 7%;

[0026] As for the above-mentioned regulator, the regulator accounts for 3.0% to 15.0% of the total mass of the raw materials of the gangue autoclaved aerated concrete.

[0027] Further: The raw materials of the gangue autoclaved aerated concrete include the following components, all measured by mass:

[0028] 50-70 parts of coal gangue;

[0029] 0.65-0.75 parts of warm water at 50-60 degrees Celsius;

[0030] 3 to 15 parts of the regulator;

[0031] 12-20 parts of lime;

[0032] 10-20 parts of cement;

[0033] 2-8 parts of gypsum;

[0034] Aluminum powder 0.05-0.12 parts.

[0035] Further: the strength level of the gangue autoclaved aerated concrete meets the A2.0-A5.0 level in the following table:

[0036]

[0037] A method for preparing gangue autoclaved aerated concrete, the method comprising:

[0038] Step 1: decarbonizing the gangue, wherein the decarbonization treatment includes photoelectric separation and / or water washing flotation; after the decarbonization treatment, the carbon content of the gangue is ≤7%;

[0039] Step 2: using the raw materials of the above-mentioned gangue autoclaved aerated concrete to prepare the gangue autoclaved aerated concrete;

[0040] The strength grade of the gangue autoclaved aerated concrete meets the grade A2.0 to grade A5.0 in the following table:

[0041]

[0042] Furthermore: after the decarbonization treatment, the carbon content of the gangue is ≤3%.

[0043] Furthermore, the step 2 comprises: mixing and stirring the raw materials of the gangue autoclaved aerated concrete, and then performing pouring, stopping, cutting and demoulding, pre-curing before the autoclave, and autoclaving curing, so as to obtain the gangue autoclaved aerated concrete.

[0044] Compared with the related art, the present invention has the following advantages:

[0045] The regulator of the gangue autoclaved aerated concrete of one aspect of the present invention is selected according to the particularity of the gangue raw material, and adopts the technical methods of single admixture, double admixture and composite admixture, so that the comprehensive performance of the autoclaved aerated concrete products obtained is greatly improved. The regulator of the present invention has the function of wrapping the carbon particles of the gangue, shielding or reducing the adverse effects of the carbon factor in the gangue, and also has an activation effect at the same time, which can improve the volcanic ash activity of the gangue autoclaved aerated concrete raw material, promote the full progress of the hydration reaction, and improve the hydration quality and strength of the product. Therefore, the regulator has the functions of an activator for improving the reaction activity of the raw material for preparing autoclaved aerated concrete and a regulator for improving the strength of the product, so it has great innovative significance. The use of the regulator of the present invention is conducive to improving the durability, sealing, impermeability, corrosion resistance, impact resistance and wear resistance of the product.

[0046] The autoclaved aerated concrete prepared from coal gangue in another aspect of the present invention uses the above-mentioned regulator, which realizes the large-volume application of coal gangue in the autoclaved aerated concrete, not only effectively reducing the preparation cost of the autoclaved aerated concrete, but also solving the environmental problems caused by coal gangue, and saving the treatment cost caused by treating coal gangue. At the same time, due to the use of the above-mentioned regulator, the volcanic ash activity of the raw material for preparing autoclaved aerated concrete from coal gangue can be compensated and improved, the hydration reaction is fully promoted, the hydration quality and strength of the product are improved, and it is beneficial to improve the durability, sealing, impermeability, corrosion resistance, impact resistance and wear resistance of the product.

[0047] The method for preparing autoclaved aerated concrete from coal gangue in another aspect of the present invention uses the above-mentioned regulator to achieve the large-volume application of coal gangue in autoclaved aerated concrete, which not only effectively reduces the preparation cost of autoclaved aerated concrete, but also solves the environmental problems caused by coal gangue and saves the treatment cost caused by treating coal gangue. At the same time, the use of the above-mentioned regulator can compensate for and improve the volcanic ash activity of the raw material for preparing autoclaved aerated concrete from coal gangue, promote the full progress of the hydration reaction, improve the hydration quality and strength of the product, and help improve the durability, sealing, impermeability, corrosion resistance, impact resistance and wear resistance of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The photographs of the gangue autoclaved aerated concrete products of Experimental Examples 1-3 of one embodiment of the present invention;

[0049] FIG2 is an XRD diffraction pattern of gangue autoclaved aerated concrete according to another embodiment of the present invention; wherein (1) is the quantitative XRD pattern of 1# gangue; (2) is the quantitative XRD pattern of 2# gangue; (3) is the XRD pattern of sample No. 7 of 1# gangue (experimental example 1);

[0050] Figure 3 is a SEM photograph of gangue autoclaved aerated concrete of another embodiment of the present invention;

[0051] Figure 4 is a flow chart of physical decarbonization treatment of coal gangue raw materials according to another embodiment of the present invention;

[0052] FIG5 is a photo of a gangue autoclaved aerated concrete product of Experimental Examples 4-6 of another embodiment of the present invention; (1) is Experimental Example 6; (2) is Experimental Example 5; (3) is Experimental Example 4;

[0053] Figure 6 is a photo of a gangue autoclaved aerated concrete product of Experimental Example 7-8 of another embodiment of the present invention;

[0054] Figure 7 is the XRD diffraction pattern of 4# coal gangue material according to another embodiment of the present invention;

[0055] Figure 8 This is a photo of the appearance of Comparative Example 2. DETAILED DESCRIPTION

[0056] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below. However, it should be understood that the description herein is only used to explain the present invention and is not used to limit the scope of the present invention.

[0057] Unless otherwise defined, all technical terms and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art of the present invention. The terms used in the present invention specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The characterization means involved in this article can refer to the relevant descriptions in the prior art and will not be repeated in this article.

[0058] In order to further understand the present invention, the present invention is further described in detail below in conjunction with the best embodiment.

[0059] Gangue is a mixture of various rock blocks, and its composition is quite complex. From the perspective of chemical composition, gangue is a mixture of inorganic matter and a small amount of organic matter. Inorganic matter is mainly minerals and water, and there are dozens of elements that constitute the mineral components. Generally, SiO2 and Al2O3 are the main components. In addition, it contains varying amounts of Fe2O, CaO, MgO, SO3, K2O, Na2O, P2O3 and other inorganic substances, as well as trace amounts of rare metals (such as titanium, vanadium, cobalt, etc.). The organic matter in gangue increases with the increase of coal content, and it mainly includes carbon, hydrogen, oxygen, nitrogen and sulfur. The total content of inorganic SiO2 and Al2O3 in gangue is generally above 70%, and some exceed 90%. Among them, the SiO2 content is generally above 50%, and some reach 80%. Therefore, it is innately suitable to use gangue as a siliceous material for the production of autoclaved aerated coagulation.

[0060] However, compared with other minerals with volcanic ash activity (including fly ash from power plants), the minerals that make up coal gangue are often better crystallized, the chemical molecules are arranged in a more orderly and dense manner, and their chemical structure is relatively stable. Therefore, the volcanic ash activity of the original coal gangue is very low. At the same time, since coal gangue generally contains combustible carbon, it creates certain obstacles for the direct use of coal gangue. The carbon content of Class I and Class II coal gangue is ≤6% (the lower calorific value is below 420kcal); while the carbon content of Class III coal gangue is 6% to 20%, which is between Class II and Class IV coal gangue; the carbon content of Class IV coal gangue is ≥20%, and the calorific value is higher (lower calorific value ≥1400kcal / kg).

[0061] In long-term research, we found that the existence and structural forms of carbon in coal gangue and fly ash are very different: most of the carbon in coal gangue is mixed, interwoven, and wrapped with various minerals such as quartz, alumina, and carbonate in coal gangue, or exists in the form of various carbonate mineral phases such as calcite, mica, kaolinite, and illite; while most of the carbon in fly ash is in the form of coarse and porous coke particles or semi-coke particles, mixed with the silicon-alumina glass body (generally accounting for about 70%) and other crystalline minerals (mullite, quartz, hematite, etc.) of fly ash. Unlike fly ash, coal gangue has lower volcanic ash activity. Therefore, in order to solve the problem of preparing autoclaved aerated concrete with large amounts of coal gangue and obtain stable industrial application, it is necessary to solve the problem of coal gangue activation and the compressive strength of the obtained products in a stable, reliable, cost-effective, and suitable way for industrial application.

[0062] Example 1

[0063] like Figure 1 As shown, a regulator for gangue autoclaved aerated concrete, the regulator is selected from:

[0064] Group 1: Silica Fume;

[0065] and / or, Group 2: silica sol;

[0066] Furthermore: If the regulator uses the first group and the second group, the mass ratio of the first group to the second group is (2:3) to (5:2), for example, it can be 2:5, 1:1, 1:2, 2:3, 3:2, 3:4 or 3:5, etc., but the present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] The regulator accounts for 3.0% to 15.0% of the total mass of the raw materials of the gangue autoclaved aerated concrete, for example, it can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] The average particle size of silica fume is 0.1-0.3μm, and the fineness is less than 1μm, accounting for more than 80%, and the specific surface area is 20-28m 2 / g. Its fineness and specific surface area are about 80 to 100 times that of cement and 50 to 70 times that of fly ash.

[0069] During the formation process, silica fume is affected by surface tension during phase change, forming non-crystalline amorphous spherical particles with a relatively smooth surface, and some are agglomerates of multiple spherical particles stuck together. It is a volcanic ash material with a large specific surface area and high activity. It is dispersed in the gaps of other coarse particles and hydrated with alkaline oxides to form a gel. Under high temperature and high pressure conditions, it is easier to form tobermorite, thereby improving the strength of the product.

[0070] Using an appropriate amount of silica fume in coal gangue autoclaved aerated concrete can help to make up for the insufficiently active SiO2 in the coal gangue, increase the density of the product, increase the strength of the product, improve the durability of the product, and improve the product's anti-seepage, anti-corrosion, impact resistance and wear resistance.

[0071] Silica sol is a dispersion system containing a large number of hydrated SiO2 particles. Its greatest feature is its huge surface free energy. It has a low viscosity and can penetrate anywhere water can penetrate. Therefore, it has very good dispersibility and permeability when mixed with other substances. When the water in silica sol evaporates, the colloidal particles are firmly attached to the surface of the object, and silicon-oxygen bonds are formed between the particles, making it a very good adhesive.

[0072] In addition to utilizing its good dispersibility and permeability, the role of silica sol in gangue autoclaved aerated concrete is also beneficial to wrap the C-type powder particles with low hardness that do not participate in the hydrothermal synthesis reaction, and then react with Ca(OH)2 to form monoalkali hydrate CSH-(I) and CSH gel near the carbon particles, and then partially recrystallize into tobermorite, shielding the influence of C-type particles on the strength of the product, improving the strength and other physical properties of the product. In addition, due to the small size of silica sol particles, it is beneficial to increase the density of the pore wall of gangue steam concrete, thereby increasing the sealing and impermeability of the product and improving the physical strength of the product.

[0073] Due to the dispersibility, permeability and large specific surface area of ​​silica sol, when mixed with coal gangue raw materials to make pulp, silica sol will penetrate into the interior of coal gangue carbon particles and form a network wrapping of carbon particles. When alkaline raw materials such as cement and lime are added, since silica sol itself is nano-scale silicon dioxide, it reacts with cement and lime hydrated calcium hydroxide to generate hydrated calcium silicate CSH (I), which creates a strong bond between the raw materials (carbonaceous particles) in the body; with the implementation of the autoclave curing system, most of these hydrated calcium silicates will gradually transform into well-crystallized tobermorite, which improves the strength of coal gangue autoclaved aerated concrete, thereby avoiding or reducing the influence of carbon factors in coal gangue on the strength of coal gangue autoclaved aerated concrete. Therefore, silica sol also acts as a modifier for coal gangue.

[0074] Example 2

[0075] A regulator for gangue autoclaved aerated concrete, wherein the regulator is selected from:

[0076] Group 1: Silica Fume;

[0077] and / or, at least one of the second group, the third group, and the fourth group;

[0078] The second group is silica sol;

[0079] The third group is sodium tripolyphosphate;

[0080] The fourth group is at least one of glass fiber powder, hydroxypropyl methylcellulose, and lignin sulfonate;

[0081] The regulator accounts for 3.0% to 15.0% of the total mass of the raw materials of the gangue autoclaved aerated concrete, for example, it can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0082] Further: if the regulator includes the first group and the third group, the mass ratio of the first group to the third group is 5:2;

[0083] Furthermore: If the regulator includes a first group and a fourth group, the mass ratio of the first group to the fourth group is (5:1) to (5:4), for example, it can be 5:1, 5:2, 5:3 or 5:4. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] After research, it was found that the ratio of the above regulators can obtain better compressive strength of products. The use of regulators can be based on actual conditions. They can be used alone, in pairs or in multiples. Mixed use can not only reduce costs, but also exert synergistic effects to achieve better product strength.

[0085] The regulator includes the first group and the third group, for example, the regulator is the first group and the third group, or the regulator is the first group, the second group, and the third group; or, the regulator is the first group, the second group, the third group, and the fourth group; and other combinations including the first group and the third group.

[0086] The regulators include the first group and the fourth group, for example, the regulators are the first group and the fourth group, or the regulators are the first group, the second group, and the fourth group; or, the regulators are the first group, the second group, the third group, and the fourth group; and other combinations including the first group and the fourth group.

[0087] Preferably, the conditioning agent is silica fume;

[0088] Or, the conditioning agent is silica fume and silica sol;

[0089] Or, the regulator is silica fume or sodium tripolyphosphate;

[0090] Or, the conditioning agent is silica fume or glass fiber powder;

[0091] Or, the conditioning agent is silica fume or hydroxypropyl methylcellulose;

[0092] Or, the conditioning agent is silica fume or lignin sulfonate;

[0093] Or, the regulator is silica sol;

[0094] Or, the regulator is silica fume, silica sol, sodium tripolyphosphate;

[0095] Or, the conditioning agent is silica fume, silica sol, or glass fiber powder;

[0096] However, the present invention is not limited to the listed combinations, and other combinations not listed are also applicable within the scope of the above description of the regulator of the present invention.

[0097] The aqueous solution of sodium tripolyphosphate is quite stable at room temperature, but due to the promotion of hydrolysis by heating, acid and alkali, the content of sodium tripolyphosphate will become less and less, and sodium tripolyphosphate will return to the original orthophosphate. The hydrolysis reaction is as follows:

[0098] Na5P3O 10 +H2O→Na2HPO4+NaH2PO4

[0099] For example, at 80°C, sodium tripolyphosphate hexahydrate is stable, at 85-120°C it is dehydrated and decomposed into sodium dihydrogen phosphate and sodium pyrophosphate, and at above 120°C it is re-synthesized into sodium tripolyphosphate.

[0100] Sodium tripolyphosphate has many excellent properties and is suitable for use in gangue autoclaved aerated concrete. First, it can play a complexing role on metal ions in the raw materials to avoid the aggregation of metal objects and cause uneven density of the product; second, because of its strong dispersion power on solid particles, it can stimulate the activity and dissolution of SiO2 and CaO in the raw materials, promote the full progress of hydration reaction, and improve the hydration quality and strength of the product; third, it increases the fluidity of the slurry and promotes the stability of hydrolysis.

[0101] Glass fiber powder is made by chopping, grinding and screening specially drawn continuous glass fiber strands. It is widely used as a filling and reinforcing material in various thermosetting resins and thermoplastic resins.

[0102] Performance index: Density: 2.254g / cm 3, moisture content: <0.5%, fiber diameter: 9-13μm, aspect ratio: 4:1-8:1, particle size: 300-400, fiber composition: E glass (alkali content <0.5%), C glass (alkali content <12%).

[0103] When used in gangue autoclaved aerated concrete, it can enhance its low-temperature crack resistance and fatigue resistance, improve the high-temperature stability of gangue autoclaved aerated concrete, and extend its service life.

[0104] Hydroxypropyl methylcellulose (Hypromellose), also known as hydroxypropyl methylcellulose, is a type of non-ionic cellulose mixed ether. Its aqueous solution has surface activity. It has high transparency and stable performance. Products of different specifications have different gel temperatures. Solubility varies with viscosity. The lower the viscosity, the greater the solubility. The dissolution of HPMC in water is not affected by pH value.

[0105] When used in coal gangue autoclaved aerated concrete, it can promote the bonding of raw materials, facilitate molding and demoulding, and increase the strength of the product.

[0106] Calcium lignin sulfonate (referred to as wood calcium) is a multi-component high molecular weight polymer anionic surfactant. It is a light yellow to dark brown powder with a slight aromatic smell. Its molecular weight is generally between 800 and 10,000. It has strong dispersibility, adhesion and chelating properties.

[0107] When used as a concrete water reducer, adding 0.25-0.3% of cement can reduce water consumption by more than 10-14%, improve the workability of concrete, significantly improve operating performance, and have good effects such as strengthening and preventing cracking.

[0108] Silica fume, silica sol and sodium tripolyphosphate are both activators and enhancers, which can promote the hydration reaction of autoclaved aerated concrete prepared from coal gangue, thereby greatly improving the compressive strength of the product. An additive with both activation and enhancement effects solves the problem of using large amounts of coal gangue in the preparation of autoclaved aerated concrete. The preparation method is stable and reliable and can be applied industrially, solving the long-standing problem of industrial application of autoclaved aerated concrete prepared from coal gangue, and therefore has great innovative significance.

[0109] Glass fiber powder, hydroxypropyl methylcellulose and calcium lignin sulfonate play a role in fiber reinforcement. It can be understood that the addition of sodium tripolyphosphate, glass fiber powder, hydroxypropyl methylcellulose and lignin sulfonate is a further improvement on the silica fume and silica sol solution, and only silica fume or silica sol can be used as a regulator.

[0110] Example 3

[0111] On the basis of Example 1 or 2, a gangue autoclaved aerated concrete is provided, wherein the raw materials of the gangue autoclaved aerated concrete include:

[0112] The coal gangue accounts for more than 50% of the total mass of the raw materials of the coal gangue autoclaved aerated concrete; for example, it can be 55%, 60%, 65% or 70%, and the present invention is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the carbon content of the coal gangue is less than or equal to 7%; for example, it can be 1%, 2%, 3%, 4%, 5%, 6% or 7%, and the present invention is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0113] The regulator described in Example 1 or 2 accounts for 3.0% to 15.0% of the total mass of the raw materials of the gangue autoclaved aerated concrete, for example, it can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0114] Example 4

[0115] On the basis of Example 3, further: the raw materials of the gangue autoclaved aerated concrete include the following components, all calculated by mass:

[0116] The coal gangue may be 50 to 70 parts; for example, it may be 50, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64 or 70. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0117] 0.65-0.75 parts of warm water at 50℃-60℃; for example, it can be 50℃, 52℃, 54℃, 56℃, 58℃ or 60℃ warm water, and the present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable; the number of parts of warm water can be, for example, 0.65, 0.66, 0.67, 0.68, 0.69, 0.7, 0.71, 0.72, 0.73, 0.74 or 0.75 parts, and the present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0118] The regulator is 3 to 15 parts; for example, it can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 parts. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0119] 12 to 20 parts of lime; for example, it can be 12, 13, 14, 15, 16, 17, 18, 19 or 20 parts. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0120] 10 to 20 parts of cement; for example, it can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 parts. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0121] 2 to 8 parts of gypsum; for example, it can be 2, 3, 4, 5, 6, 7 or 8 parts. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0122] Aluminum powder 0.05-0.12 parts. For example, it can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11 or 0.12 parts. The present invention is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0123] Cement and lime are the main sources of calcium raw materials for gangue autoclaved aerated concrete, accounting for about 30% of the product weight.

[0124] Further: the strength level of the gangue autoclaved aerated concrete meets the A2.0-A5.0 level in the following table:

[0125]

[0126]

[0127] Example 5

[0128] On the basis of Example 3 or 4, a method for preparing gangue autoclaved aerated concrete is provided, wherein the autoclaved aerated concrete is prepared using the raw materials of the gangue autoclaved aerated concrete; the method comprises:

[0129] Step 1: decarbonizing the coal gangue, wherein the decarbonization treatment includes: photoelectric separation and / or water washing flotation;

[0130] After the decarbonization treatment, the carbon content of the gangue is less than or equal to 7%; for example, it can be 1%, 2%, 3%, 4%, 5%, 6% or 7%. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0131] Step 2: Mix and stir the raw materials of the gangue autoclaved aerated concrete described in Example 3 or 4, and then perform pouring, static stopping, cutting and demoulding, pre-curing before the autoclave, and autoclaving curing to obtain the gangue autoclaved aerated concrete;

[0132] The strength grade of the gangue autoclaved aerated concrete meets the grade A2.0 to grade A5.0 in the following table, for example, it can be grade A2.0, grade A2.5, grade A3.5 or grade A5.0.

[0133] Table 1 Compressive strength and dry density requirements

[0134]

[0135]

[0136] The above table is selected from "GB / T11968-2020 Autoclaved Aerated Concrete Blocks".

[0137] Practice has shown that the carbon content of coal gangue below 3% after electro-optical sorting and water washing flotation has almost no significant effect on the production of products (see Figure 1 This experiment uses 3# raw material). When using coal gangue raw materials after photoelectric dry separation to prepare autoclaved aerated concrete, for raw materials with a carbon content of more than 7%, water washing and flotation must be further processed to obtain raw materials with a carbon content of less than 7%, thereby obtaining good use conditions. Therefore, multi-stage physical decarbonization such as electro-optical separation and water washing and flotation is used to make the carbon content of coal gangue ≤7%, so that the coal gangue above 7% can meet the use conditions after secondary separation, thereby expanding the scope of coal gangue utilization and fundamentally solving the problem of resource utilization of coal gangue.

[0138] When the carbon content of gangue is less than or equal to 7%, a better qualified product can be prepared by using a regulator (reinforcer) or a combination of multiple regulators (reinforcers), and the compressive strength of the product can be significantly enhanced. The fine coal gangue with a carbon content of less than 7% obtained by decarbonization by the above physical method is further ball-milled to a particle size of 200 mesh sieve residue ≤15%, and then the subsequent raw material mixing steps are carried out.

[0139] The XRD diffraction spectrum of the autoclaved aerated concrete sample of the coal gangue of the present invention shows that the main mineral components in the sample are tobermorite, CSH gel, anhydrite, quartz, dolomite, calcite, carbon siliceous limestone, pseudowollastonite, halloysite and other minerals (see Figure 2).

[0140] like Figure 3 As shown in Figure 2, through SEM scanning electron microscope observation, the hydrothermal synthesis products of coal gangue autoclaved aerated concrete are mainly flaky tobermorite, needle-shaped CSH and hydrated calcium sulfoaluminate, etc. and other unreacted minerals. CSH gel mixes and interweaves a large number of high-strength tobermorite crystals with other substances, and the distribution of unreacted minerals is not too concentrated, so the strength and stability of the product are well guaranteed.

[0141] like Figure 4 As shown, the beneficial effects of the physical decarbonization method used in one embodiment of the present invention are described as follows:

[0142] (1) The calorific value of black gangue selected by the photoelectric sorter is about 3200 kcal or more. The company recycles and sells it as energy. The current market price is 300 yuan / t. A production line with a daily processing capacity of 2,000 tons of gangue can recycle about 400 tons of black gangue with a higher calorific value per day, which can generate revenue of about 120,000 yuan;

[0143] (2) The carbon content of the white gangue (raw material with slightly higher calcium and magnesium content) selected by the photoelectric sorter is about 10% (calorific value is about 650kcal), which is the No. 2 material used in this test. When the sorting effect is very good, the carbon content of the white gangue (raw material with slightly higher calcium and magnesium content) can be controlled below 5% (calorific value ≤ 350kcal / kg), which is the No. 1 material used in this test. A production line with a daily processing capacity of 2,000 tons of coal gangue can sort about 300 tons of white gangue calcium and magnesium materials per day, which are hammer crushed / screened and used as raw materials for autoclaved aerated concrete (which can meet the annual production of 1 million m 3 Materials for large-scale autoclaved aerated concrete production);

[0144] (3) The calorific value of the gangue raw material after the black gangue coal carbon and white gangue calcium and magnesium materials are selected by the photoelectric sorter is about 900kcal. A production line with a daily processing capacity of 2,000 tons of gangue can sort about 500 tons of gangue raw materials per day. After hammer crushing / screening, it can be directly used as the raw material for sintered bricks (which can meet the material needs of a production line with an annual output of 150 million sintered bricks);

[0145] (4) The calorific value of the fine material sorted by the 1.5 cm roller screen is about 1350 kcal. A production line with a daily processing capacity of 2,000 tons of coal gangue can produce about 800 tons of sorted fine material per day, which can be sold to cement plants, sintered brick and stone companies as low calorific value fuel to generate income for the companies. At the same time, it can also be used as a raw material for autoclaved aerated concrete after further water washing (flotation).

[0146] (5) If all the fine materials separated by 1.5cm roller screen are washed and floated, about 300t / day of coal slime with calorific value above 3000kcal / kg can be selected, which can generate another 90,000 yuan / day for the enterprise. The daily output of fine materials after water washing (flotation) is about 500t, and the carbon content in the fine materials will be less than 3% (below 200kcal / kg). This is the No. 3 material used in this test. If it is used or mixed in autoclaved aerated concrete raw materials or sintered hollow brick raw materials, the impact of coal carbon will be further reduced, which will reduce the pressure on production.

[0147] If conditions permit, all raw materials (2), (3) and (4) after photoelectric dry separation can be further washed (flotation), which is more conducive to the purity of the raw materials for coal gangue autoclaved aerated concrete and sintered hollow bricks, reducing the impact of carbon content on the production quality of the two ecological building materials and improving the compressive strength of the products.

[0148] The flotation reagent for water washing flotation is prepared through experiments according to the type of coal gangue to be flotated, and its dosage is determined according to the amount of coal gangue to be processed. The flotation reagent is purchased from a commercially available flotation reagent manufacturer.

[0149] Water washing flotation is also known as wet water washing technology. Its process is as follows: the fine material (screened material) of coal gangue after hammer crushing is mixed with reagents and put into the flotation machine to separate the gangue minerals from organic matter such as coal powder. The separated organic matter such as coal powder can be used or sold as fuel. The gangue and other minerals obtained after separation are used as raw materials for autoclaved aerated concrete.

[0150] Furthermore: after the decarbonization treatment, the carbon content of the gangue is ≤3%, for example, 0.10%, 0.20%, 0.30%, 0.40%, 0.50%, 0.60%, 0.70%, 0.80%, 0.90%, 1.00%, 2.00%, 2.50% or 3%. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0151] Example 6

[0152] The present invention is further described below with experimental examples:

[0153] When the raw coal gangue enters the factory, the carbon content is above 20% and the calorific value is above 1500kcal / kg:

[0154] After photoelectric sorting, the carbon content of the gangue is reduced to about 10%, and the calorific value is about 750kcal / kg (the 2# material used in this experiment comes from this); when the sorting process is different or the sorting effect is particularly good, the carbon content of the gangue is reduced to about 5%, and the calorific value is about 350kcal / kg (the 1# material used in this experiment also comes from this). After the photoelectric sorting of the gangue, after water washing and flotation, the carbon content of the gangue can be reduced to less than 3%, and the calorific value is less than 200kcal / kg (the 3# material used in this experiment).

[0155] Although the gangue after physical decarbonization treatment is hammered and screened again, the raw material particle size is generally coarse and cannot meet the particle size requirements required for the hydration reaction of the main raw materials of gangue autoclaved aerated concrete. The fine gangue used for gangue autoclaved aerated concrete needs to be further deep-ground by a mining mill to make its particle size reach 200 sieve residue ≤15%, which is also a necessary measure for mechanical activation of gangue raw materials. When using the dry grinding process, attention should be paid to environmental protection measures to prevent dust from flying; when using the wet grinding process, the purpose of fine grinding of raw materials and preparation of slurry can be achieved at one time.

[0156] When using coal gangue raw materials after photoelectric dry separation to prepare autoclaved aerated concrete, for raw materials with a carbon content of more than 7%, in principle, continued enhanced physical decarbonization measures must be adopted, which is not advisable in principle.

[0157] For raw materials with a carbon content of more than 7%, if no further carbon reduction technical measures are adopted, it is found that the appearance of the products is not well maintained after demoulding, the mechanical strength is poor, and the bubbles are very controlled.

[0158] Although for raw materials with a carbon content of 3% to 7% (see raw material No. 1 in this test), in general, qualified coal gangue autoclaved aerated concrete can be prepared without adding auxiliary agents, but by using a regulator (reinforcer) or a combination of multiple regulators (reinforcers), better qualified products can be prepared and the compressive strength of the products can be greatly improved.

[0159] After the above pre-treatment, the chemical composition of the gangue raw materials used for gangue autoclaved aerated concrete is as follows:

[0160] Table 2 Chemical composition of gangue raw materials used for gangue autoclaved aerated concrete

[0161] Coal Gangue <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[Na2O]]> <![CDATA[K2O]]> <![CDATA[SO3]]> C 1#(%) 61.79 10.28 5.84 9.07 4.44 0.62 1.80 2.06 3.7 2#(%) 48.46 14.73 7.37 8.65 3.93 0.29 1.90 1.85 6.8 3#(%) 76.73 13.96 3.45 3.15 0.06 -- 1.55 0.10 -- 4#(%) 36.18 12.09 13.53 19.24 3.57 0.26 1.67 2.92 10.9

[0162] After the above pre-treatment, the mineral composition of the gangue raw material used for gangue autoclaved aerated concrete is as follows:

[0163] Table 3 Mineral composition of coal gangue raw materials

[0164]

[0165] The composition of cement and lime used in the present invention is as follows:

[0166] Table 4 Composition of cement and lime materials

[0167]

[0168] The other materials used in the present invention are as follows:

[0169] plaster:

[0170] This test uses analytically pure dihydrate gypsum from Fuchen Company, with a CaSO4·2H2O content of ≥99%.

[0171] Aluminum powder:

[0172] This test uses metal aluminum powder, which is still normally used by most autoclaved aerated concrete companies, as the gas generating agent.

[0173] Silica Fume:

[0174] Provided by a company in Ningxia, SiO2 content ≥ 93%, specific surface area ≥ 18m 2 / g

[0175] Silica Sol:

[0176] This test uses S-1430B water glass type silica sol, the performance indicators are as follows:

[0177] Table 5 Performance indexes of water glass type silica sol

[0178] <![CDATA[SiO2]]> <![CDATA[Na2O]]> Specific gravity (25℃) <![CDATA[Viscosity (25°C, mm 2 / S)]]> Average particle size (nm) Stable period 29~31 ≤0.5 1.19~1.21 ≤6.5 10~16 ≥ 1 year

[0179] The compressive strength test method of the present invention uses a destructive test, which is a method of testing a material under a pressure exceeding its limit. The purpose of this test method is to evaluate the ultimate compressive resistance of the material and to record and analyze the material's destruction process. In common destructive tests, a press machine is usually used to evaluate the compressive strength of a building structure. The compressive strength test equipment model used in the experiment of the present invention is: RFP-03 intelligent dynamometer.

[0180] Experimental Example 1:

[0181] Formula and preparation process of 1# raw material (carbon content 3.7%) + 3% silica fume (C / S = 0.62):

[0182] (1) Add 58.3 parts of material 1#, 3 parts of silica fume, and 0.65 parts of 60°C warm water and stir for 5 minutes;

[0183] (2) While stirring continuously, quickly add 16 parts of lime, 18.9 parts of cement, and 3.8 parts of gypsum and continue stirring for 2.5 minutes;

[0184] (3) Add 0.09 parts of aluminum powder while stirring for 40 seconds;

[0185] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0186] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3.0 hours to complete the static stop processes of foaming, shaping, and solidification;

[0187] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0188] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80° C. and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 4 hours;

[0189] (8) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing. The curing system is: room temperature ~ 105℃ uniform heating for 10min, 105 ~ 125℃ uniform heating for 75min, 125 ~ 190℃ uniform heating for 75min, 190℃ (autoclave pressure 1.25MPa) constant temperature for 8h, uniform exhaust and pressure reduction (cooling) for 2h until the pressure in the autoclave drops to 0 (the temperature is still above 110℃), and the autoclave is taken out when the temperature in the autoclave drops to a safe temperature below 60℃ (to prevent scalding).

[0190] The absolute dry density is 528kg / m 3 Its compressive strength reaches 2.71Mpa (see sample 7#).

[0191] Experimental Example 2:

[0192] Formula and preparation process of 1# raw material (carbon content 3.7%) + 3% silica sol (C / S = 0.62):

[0193] (1) Add 61.3 parts of material 1#, 3 parts of silica sol, and 0.65 parts of 60°C warm water and stir for 5 minutes;

[0194] (2) While stirring continuously, quickly add 16 parts of lime, 18.9 parts of cement, and 3.8 parts of gypsum and continue stirring for 2.5 minutes;

[0195] (3) Add 0.09 parts of aluminum powder while stirring for 40 seconds;

[0196] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0197] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3 hours to complete the static stop processes of foaming, shaping, and solidification;

[0198] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0199] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80° C. and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 4 hours;

[0200] (8) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing. The curing system is: room temperature ~ 105℃ uniform heating for 10min, 105 ~ 125℃ uniform heating for 75min, 125 ~ 190℃ uniform heating for 75min, 190℃ (autoclave pressure 1.25MPa) constant temperature for 8h, uniform exhaust and pressure reduction (cooling) for 2h until the pressure in the autoclave drops to 0 (the temperature is still above 110℃), and the autoclave is taken out when the temperature in the autoclave drops to a safe temperature below 60℃ (to prevent scalding).

[0201] The absolute dry density is 526kg / m 3 Its compressive strength reaches 2.81Mpa (see 5# sample).

[0202] Experimental Example 3:

[0203] Formula and preparation process of 1# raw material (carbon content 3.7%) + 3% silica sol + 3% silica fume (C / S = 0.62):

[0204] (9) Add 58.3 parts of material 1#, 3 parts of silica sol, 3 parts of silica fume, and 0.65 parts of 60°C warm water and stir for 5 minutes;

[0205] (10) While stirring continuously, quickly add 16 parts of lime, 18.9 parts of cement, and 3.8 parts of gypsum and continue stirring for 2.5 minutes;

[0206] (11) Add 0.09 parts of aluminum powder while stirring for 40 seconds;

[0207] (12) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0208] (13) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3.0 h to complete the static stop processes of foaming, shaping, and solidification;

[0209] (14) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0210] (15) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80° C. and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 6 h;

[0211] (16) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing. The curing system is: room temperature ~ 105 ° C uniform heating for 10 minutes, 105 ~ 125 ° C uniform heating for 75 minutes, 125 ~ 190 ° C uniform heating for 75 minutes, 190 ° C (autoclave pressure 1.25MPa) constant temperature for 8 hours, uniform exhaust and pressure reduction (cooling) for 2 hours until the pressure in the autoclave drops to 0 (the temperature is still above 110 ° C), and the autoclave is taken out when the temperature in the autoclave drops to a safe temperature below 60 ° C (to prevent scalding).

[0212] The absolute dry density is 543kg / m 3 Its compressive strength reaches 3.02Mpa (see sample 8#)

[0213] Experimental Example 4:

[0214] 2# raw material (carbon content 6.9%, 483kcal / kg) + silica fume + silica sol + glass fiber powder (C / S = 0.78);

[0215] (1) Add 60 parts of 2# raw material, 5 parts of silica fume, 3 parts of silica sol, 3 parts of glass fiber powder, and 0.75 parts of 60℃ warm water and stir for 10 minutes;

[0216] (2) While stirring continuously, quickly add 16 parts of lime, 16 parts of cement, and 3 parts of gypsum and continue stirring for 2.5 minutes;

[0217] (3) Add 0.09 parts of aluminum powder while stirring for 40 seconds;

[0218] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0219] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3 hours to complete the static stop processes of foaming, shaping, and solidification;

[0220] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0221] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80° C. and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 8 hours;

[0222] (8) The pre-cured green body is quickly sent to a small autoclave for autoclave curing (the hydrothermal synthesis reaction continues to occur inside the green body to generate sufficient hydration products and reach the necessary crystallinity, so that the product has good performance). The curing system is: uniform temperature rise from room temperature to 105°C for 10 minutes (during which the relief valve is in the open state), uniform temperature rise from 105 to 125°C for 75 minutes, uniform temperature rise from 125 to 190°C for 75 minutes, constant temperature at 190°C (autoclave pressure 1.25MPa) for 8 hours, uniform exhaust and depressurization for 2 hours, and the autoclave pressure drops to 0. When the humidity in the autoclave drops to a safe temperature below 60°C, the autoclave is removed from the autoclave.

[0223] The absolute dry density is 542kg / m 3 , its compressive strength reaches 2.89Mpa.

[0224] Experimental Example 5:

[0225] Formula of 2# raw material (carbon content 6.9%, calorific value 483kcal / kg) + silica fume + sodium tripolyphosphate (C / S=0.78);

[0226] (1) Add 60 parts of 2# material, 5 parts of silica fume, 2 parts of sodium tripolyphosphate, and 0.75 parts of 60°C warm water and stir for 10 minutes;

[0227] (2) While stirring continuously, quickly add 16 parts of lime, 16 parts of cement, and 3 parts of gypsum and continue stirring for 2.5 minutes;

[0228] (3) Add 0.09 parts of aluminum powder while stirring for 40 seconds;

[0229] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0230] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3 hours to complete the static stop processes of foaming, shaping, and solidification;

[0231] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0232] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80°C and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 10 hours;

[0233] (8) The pre-cured green body is quickly sent to the autoclave for autoclave curing (the hydrothermal synthesis reaction continues to occur inside the green body to generate sufficient hydration products and reach the necessary crystallinity, so that the product has good performance). The curing system is: room temperature ~ 105℃ for 10 minutes (during which the relief valve is in the open state), 105 ~ 125℃ for 75 minutes, 125 ~ 190℃ for 75 minutes, 190℃ (autoclave pressure 1.25MPa) constant temperature for 8 hours, uniform exhaust and pressure reduction for 2 hours, and the autoclave pressure drops to 0. When the humidity in the autoclave drops to a safe temperature below 60℃, the autoclave is removed.

[0234] The absolute dry density is 539kg / m 3 , its compressive strength reaches 2.78Mpa.

[0235] Experimental Example 6:

[0236] Silica ash + silica sol formula

[0237] 2# raw material (carbon content 6.9%, calorific value 483kcal / kg) formula of silica fume + silica sol (C / S = 0.78);

[0238] (1) Add 60 parts of 2# material, 5 parts of silica fume + 3 parts of silica sol, and 0.75 parts of 60℃ warm water and stir for 10 minutes;

[0239] (2) While stirring continuously, quickly add 16 parts of lime, 16 parts of cement, and 3 parts of gypsum and continue stirring for 2.5 minutes;

[0240] (3) Add 0.09 parts of aluminum powder while stirring for 40 seconds;

[0241] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0242] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3.0 hours to complete the static stop processes of foaming, shaping, and solidification;

[0243] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0244] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80°C and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 12 hours;

[0245] (8) The pre-cured green body is quickly sent to a small autoclave for autoclave curing (the hydrothermal synthesis reaction continues to occur inside the green body to generate sufficient hydration products and reach the necessary crystallinity, so that the product has good performance). The curing system is: uniform temperature rise from room temperature to 105°C for 10 minutes (during which the relief valve is in the open state), uniform temperature rise from 105 to 125°C for 75 minutes, uniform temperature rise from 125 to 190°C for 75 minutes, constant temperature at 190°C (autoclave pressure 1.25MPa) for 8 hours, uniform exhaust and depressurization for 2 hours, and the autoclave pressure drops to 0. When the humidity in the autoclave drops to a safe temperature below 60°C, the autoclave is removed from the autoclave.

[0246] The absolute dry density is 546kg / m 3 , its compressive strength reaches 2.86Mpa.

[0247] Experimental Example 7:

[0248] Silica ash + silica sol formula

[0249] 4# raw material (carbon content 10.9%, calorific value 766kcal / kg) formula of silica fume + silica sol (C / S = 0.83);

[0250] (1) Add 52 parts of 4# material, 8 parts of silica fume + 5 parts of silica sol, and 0.75 parts of 60℃ warm water and stir for 10 minutes;

[0251] (2) While stirring continuously, quickly add 18 parts of lime, 14 parts of cement, and 3 parts of gypsum and continue stirring for 2.5 minutes;

[0252] (3) Add 0.12 parts of aluminum powder while stirring for 45 seconds;

[0253] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0254] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 2.5 hours to complete the static stop processes of foaming, shaping, and solidification;

[0255] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0256] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80°C and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 12 hours;

[0257] (8) The pre-cured green body is quickly sent to the large autoclave on the production line for autoclave curing (so that the hydrothermal synthesis reaction inside the green body continues to accelerate, sufficient hydration products are generated and the necessary crystallinity is achieved, so that the product has good performance). The curing system is: in the autoclave on the production line, the air in the autoclave is replaced by steam from other autoclaves, and the air in the autoclave is exhausted for 30 minutes. At this time, the temperature in the autoclave has evenly risen to about 105°C, and the temperature is uniformly increased from 105 to 190°C for 120 minutes, and the temperature is kept constant at 190°C (autoclave pressure 1.25MPa) for 8 hours, and the steam is slowly exhausted (the steam in the autoclave is replaced by other autoclaves) for about 60 minutes, and the autoclave pressure drops to 0.80Mpa. At this time, the temperature in the autoclave is about 160°C. Then the exhaust is uniformly discharged and the pressure is reduced for 1.0h until the autoclave pressure drops to 0, and the autoclave temperature drops below 130°C before the product is taken out of the autoclave.

[0258] The absolute dry density is 547kg / m 3 , its compressive strength reaches 2.65Mpa.

[0259] Experimental Example 8:

[0260] Silica ash + silica sol + hydroxypropyl methylcellulose formula

[0261] 4# raw material (carbon content 10.9%, calorific value 766kcal / kg) formula of silica fume + silica sol + hydroxypropyl methylcellulose (C / S = 0.81);

[0262] (1) Add 55 parts of 4# material, 5 parts of silica fume, 3 parts of silica sol, and 3 parts of hydroxypropyl methylcellulose, and add 0.75 parts of 60°C warm water and stir for 10 minutes;

[0263] (2) While stirring continuously, quickly add 18 parts of lime, 14 parts of cement, and 3 parts of gypsum and continue stirring for 2.5 minutes;

[0264] (3) Add 0.010 parts of aluminum powder while stirring for 45 seconds;

[0265] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0266] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3.0 hours to complete the static stop processes of foaming, shaping, and solidification;

[0267] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0268] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80°C and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 12 hours;

[0269] (8) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing (so that the hydrothermal synthesis reaction inside the green body continues to accelerate, sufficient hydration products are generated and the necessary crystallinity is achieved, so that the product has good performance). The curing system is: in the autoclave on the production line, the air in the autoclave is replaced by steam from other autoclaves, and the air in the autoclave is exhausted for 30 minutes. At this time, the temperature in the autoclave has evenly risen to about 105°C, and the temperature is uniformly increased from 105 to 190°C for 120 minutes, and the temperature is kept constant at 190°C (autoclave pressure 1.25MPa) for 8 hours, and the steam is slowly exhausted (the steam in the autoclave is replaced by other autoclaves) for about 60 minutes, and the autoclave pressure drops to 0.80Mpa. At this time, the temperature in the autoclave is about 160°C. Then the exhaust is uniformly exhausted and the pressure is reduced and the temperature is reduced for 1.0h until the autoclave pressure drops to 0. When the temperature in the autoclave drops below 130°C, the autoclave is taken out.

[0270] The absolute dry density is 421kg / m 3 , its compressive strength reaches 2.02Mpa.

[0271] Comparative Example 1:

[0272] The steps of Example 2 are the same as those of Example 2 except that no regulator is added. The absolute dry density is 539 kg / m 3 , its compressive strength reaches 2.32Mpa, which is lower than the compressive strength of the product in Example 2.

[0273] Comparative Example 2

[0274] The steps of Example 8 are the same as those of Example 2 except that the regulator is not added. The absolute dry density is 539 kg / m 3 , and its compressive strength reaches 1.278Mpa, which is much lower than the compressive strength of the product in Example 8.

[0275] Table 6 Relationship between the performance of the gangue autoclaved aerated concrete of the present invention and the regulator

[0276]

[0277] As can be seen from Table 6, the compressive strength of the gangue autoclaved aerated concrete obtained by using the regulator of the present invention is significantly improved compared with the method without using the regulator under the same conditions. The products prepared by the method of the present invention can meet the compressive strength requirements of B05 in the national standard GB / T11968-2020 (see Table 7). At the same time, the compressive strength of the autoclaved aerated concrete prepared by using a mixed regulator is better than that of a single regulator, which shows that the double-doping and multi-doping of the regulator has a significant promoting effect on the quality of the product. It can also be seen from Table 6 that the 4# material with low silicon oxide content (36.18%) and high carbon content (10.9%), after adding the regulator, not only broke through the industry's convention that siliceous raw materials with a silicon oxide content of less than 40% cannot prepare autoclaved aerated concrete, but also the compressive strength of the product reaches the excellent standard of A2.5 grade B05 in Table 7 (Example 7). The compressive strength of the product with the same carbon content corresponding to Comparative Example 2 is far from reaching the strength standard. Example 8, due to its different formula, has different density grades, and the compressive strength has reached the A2.0 grade B04 standard in Table 6. Among them, A represents the strength grade and B represents the density grade. This is because the quality of the prepared product is generally unqualified when the coal gangue with the above carbon content is added to the autoclaved aerated concrete raw material in a large amount. Due to the addition of the above regulator, the compressive strength of the product is greatly enhanced, so that the coal gangue with the above carbon content can also be used, and the cost of processing the carbon content of the coal gangue is also reduced.

[0278] In the preparation of autoclaved aerated concrete, the density grade is mainly related to the adjustment of pores. Therefore, if a specimen of any density grade is successfully prepared at the same strength grade, it can be inferred that qualified products of other density grades at the same strength grade can also be obtained by adjusting the density grade.

[0279] Table 7 Compressive strength and dry density requirements

[0280]

[0281] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A conditioning agent for gangue autoclaved aerated concrete, characterized in that: The regulator is selected from: Group 1: Silica Fume; and / or, Group 2: silica sol; The regulator accounts for 3.0% to 15.0% of the total mass of the raw materials of the gangue autoclaved aerated concrete.

2. The regulator according to claim 1, characterized in that: If the regulators are a first group and a second group, the mass ratio of the first group to the second group is (2:3) to (5:2).

3. A conditioning agent for gangue autoclaved aerated concrete, characterized in that: The regulator is selected from: Group 1: Silica Fume; and / or, at least one of the second group, the third group, and the fourth group; The second group is silica sol; The third group is sodium tripolyphosphate; The fourth group is at least one of glass fiber powder, hydroxypropyl methylcellulose, and lignin sulfonate; The regulator accounts for 3.0% to 15.0% of the total mass of the raw materials of the gangue autoclaved aerated concrete.

4. The regulator according to claim 3, characterized in that: If the regulator includes the first group and the third group, the mass ratio of the first group to the third group is 5:2; If the regulator includes the first group and the fourth group, the mass ratio of the first group to the fourth group is (5:1) to (5:4).

5. A coal gangue autoclaved aerated concrete, characterized in that: The raw materials of gangue autoclaved aerated concrete include: Coal gangue, the mass of the coal gangue accounts for more than 50% of the total mass of raw materials of the coal gangue autoclaved aerated concrete; the carbon content of the coal gangue is less than or equal to 7%; The regulator according to any one of claims 1 to 4, wherein the regulator accounts for 3.0% to 15.0% of the total mass of the raw materials of the gangue autoclaved aerated concrete.

6. The gangue autoclaved aerated concrete according to claim 5, characterized in that: The raw materials of the gangue autoclaved aerated concrete include the following components, all measured by mass: 50-70 parts of coal gangue; 0.65-0.75 parts of warm water at 50-60°C; 3 to 15 parts of the regulator; 12-20 parts of lime; 12-20 parts of cement; 2-8 parts of gypsum; Aluminum powder 0.05-0.12 parts.

7. The gangue autoclaved aerated concrete according to claim 5 or 6, characterized in that: The strength grade of the gangue autoclaved aerated concrete meets the grade A2.0 to grade A5.0 in the following table:

8. A method for preparing gangue autoclaved aerated concrete, characterized in that: The method comprises: Step 1: decarbonizing the coal gangue, wherein the decarbonization treatment includes: photoelectric separation and / or water washing flotation; After the decarbonization treatment, the carbon content of the gangue is ≤7%; Step 2: using the raw material of the gangue autoclaved aerated concrete as claimed in claim 5 or 6 to prepare the autoclaved aerated concrete; The strength grade of the gangue autoclaved aerated concrete meets the grade A2.0 to grade A5.0 in the following table:

9. The method for preparing gangue autoclaved aerated concrete according to claim 8, characterized in that: After the decarbonization treatment, the carbon content of the gangue is ≤3%.

10. The method for preparing gangue autoclaved aerated concrete according to claim 8, characterized in that: The step 2 comprises: mixing and stirring the raw materials of the gangue autoclaved aerated concrete, and then performing pouring, stopping, cutting and demoulding, pre-curing before the autoclave, and autoclaving curing, so as to obtain the autoclaved aerated concrete.

Citation Information

Patent Citations

  • Autoclaved aerated concrete plate and molding process thereof

    CN108585653A

  • Non-autoclaved aerated phosphogypsum-based concrete block preparation method

    CN109354509A

  • Autoclaved aerated concrete plate and preparing method thereof

    CN109626932A

  • Industrial solid waste autoclaved aerated concrete block and preparation method thereof

    CN111807858A

  • Non-autoclaved aerated concrete and preparation method thereof

    CN112430050A